Different methods of determining the market value of Belarusian banks - Vasileuski, Anton V. (Journal of the Belarusian State University. Economics, 2018)
The purpose of the paper is to explore the modern world and domestic banking business valuation approaches and to identify the model that is most suitable for Belarus. Object of research is the process of determining the market price of a commercial bank in Belarus. Subject of research is the methods of valuation of the bank according to the modern Belarusian conditions. The relevance of this work is high, as due to an increase in competition in the banking sector and the deteriorating economic situation in many international banks frequent mergers and acquisitions in the banking sector are expected. These transactions require the valuation of fair true prices for commercial banks.